MOTIF TRADISI GAYA SURAKARTA Eksistensi Dan Pengembangannya Pada Ukir Kayu - Rahayu Adi Prabowo (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
The existence of a wealth of ornament in Nusantara is a challenge in terms of recognition and learning. One important element is that learning can be accepted and understood easily so that the empowerment and development of traditional motifs, especially the Surakarta style, will experience development. Traditional motifs come from classical art or primitive art, but after receiving certain treatments, their benefits are preserved to meet needs, especially in terms of aesthetic needs. One of the motifs that are often found is those applied to wood craft products (wood carvings). The wood carving motifs in Indonesia have a rich variety of styles. The various forms of carving motifs each have their own characteristics according to the region. Like the Surakarta style carving motif, which is the focus of this study, it is known to have a strong and distinctive character that is needed by a series of actions in the framework of its preservation and development. To recognize or learn the characteristics and application of Surakarta-style wood carving, it is necessary to have a mature and structured visual identification so that it is able to present good and correct information. The identification in this study uses the interpretive description method with the enrichment of the hermeneutic approach. This method approach is expected to find a result of the focus of the discussion, namely the characteristics of the Surakarta-style carving motifs applied by the craftsmen and discovering the grooves and patterns of new Surakarta-style carving motifs.